Paul the Apostle ; vol. 2 a theological and exegetical study - Penna, Romano; Wahl, Thomas P. (Collegeville, MN Liturgical, 1996)
Contents : v. 2. Wisdom and folly of the Cross
Originally published in Italian in a single vol "L'apostolo Paolo : Studi di esegesi e teologia" published by Edizioni Paolini, Turin, Italy, 1991.
Keywords: Bible. N.T. Epistles of Paul -- theology; Bible. N.T. Epistles of Paul -- criticism, interpretation, etc; Paul the Apostle, Saint -- biography